Effects of Glutathione on Growth, Intestinal Antioxidant Capacity, Histology, Gene Expression, and Microbiota of Juvenile Triploid Oncorhynchus mykiss - Wang, Chang’an; Su, Baohui; Lu, Shaoxia; Han, Shicheng; Jiang, Haibo; Li, Zhuang; Liu, Yang; Liu, Hongbai; Yang, Yuhong (Frontiers in Physiology, 2021)
This study aimed to demonstrate the effects of dietary glutathione (GSH) on growth, intestinal antioxidant capacity, histology, gene expression, and microbiota in juvenile triploid rainbow trout (Oncorhynchus mykiss). Different diets (G0-control, G100, G200, G400, and G800) containing graded levels of GSH (0, 100, 200, 400, 800 mg kg-1) were fed to triplicate groups of 30 fish (initial mean weight 4.12 ± 0.04 g) for 56 days. G400 had significantly improved weight gain and feed conversion rate. Based on the broken-line regression analysis, the optimum dietary GSH level was 447.06 mg kg-1. Catalase and superoxide dismutase activities were significantly higher in G200–G800. G200 had significantly lower malondialdehyde content. The height of the intestinal muscular layer in G400 was significantly higher than that of the control group. Intestinal PepT1 and SLC1A5 gene expression was significantly increased, and the highest was observed in G400. TNF-α, IL-1β, IL-2, and IL-8 expression were significantly decreased than that of G0. Next-generation sequencing of the 16S rDNA showed a significant difference in alpha diversity whereas no differences in beta diversity. On the genus level, LefSe analysis of indicator OTUs showed Ilumatobacter, Peptoniphilus, Limnobacter, Mizugakiibacter, Chelatococcus, Stella, Filimonas and Streptosporangium were associated with the treatment diet, whereas Arcobacter, Ferrovibrio, Buchnera, Chitinophaga, Stenotrophobacter, Solimonadaceae, Polycyclovorans, Rhodococcus, Ramlibacter and Azohydromonas were associated with the control diet. In summary, feeding juvenile triploid O. mykiss 200–800 mg kg-1 GSH improved growth and intestinal health.